Current Immunotherapeutic Approaches in Pancreatic Cancer. (14th September 2011) - Koido, Shigeo; Homma, Sadamu; Takahara, Akitaka; Namiki, Yoshihisa; Tsukinaga, Shintaro; Mitobe, Jimi; Odahara, Shunichi; Yukawa, Toyokazu; Matsudaira, Hiroshi; Nagatsuma, Keisuke; Uchiyama, Kan; Satoh, Kenichi; et al.
Abstract : Pancreatic cancer is a highly aggressive and notoriously difficult to treat. As the vast majority of patients are diagnosed at advanced stage of the disease, only a small population is curative by surgical resection. Although gemcitabine-based chemotherapy is typically offered as standard of care, most patients do not survive longer than 6 months. Thus, new therapeutic approaches are needed. Pancreatic cancer cells that develop gemcitabine resistance would still be suitable targets for immunotherapy. Therefore, one promising treatment approach may be immunotherapy that is designed to target pancreatic-cancer-associated antigens. In this paper, we detail recent work in immunotherapy and the advances in concept of combination therapy of immunotherapy and chemotherapy. We offer our perspective on how to increase the clinical efficacy of immunotherapies for pancreatic cancer.